Optimizing Google Documents as an Innovation Media for Effective and Sustainable School Literacy Habits - Siti Arofah; Wiwin Yulianingsih; M. Syahidul Haq (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2026)
The low reading literacy achievement of Indonesian students, as reflected in the 2022 Programme for International Student Assessment (PISA) scores and the Education Report of SMAN 1 Ngoro Mojokerto, demonstrates the need for strategic innovation in strengthening school literacy culture. Reading and writing literacy are the main foundations for developing critical, reflective, and communicative thinking skills needed to realize the vision of Golden Indonesia 2045. This innovation project aims to (1) describe the understanding of SMAN 1 Ngoro Mojokerto residents regarding the importance of literacy, (2) analyze the implementation of the ongoing literacy culture, and (3) formulate strategies for improving literacy culture through the use of digital technology. The method used is a descriptive-qualitative approach based on best practices with document analysis, Education Report data, and evaluation of innovation programs. The innovation developed is the "Waca Beli Onday OgeDoc" program (School Residents Literacy Reading and Writing One Day on Google Docs), which integrates daily reading and writing activities for 20 minutes using the Google Docs platform. An analysis of innovation diffusion using Rogers' theory shows that this program meets five innovation attributes: relative advantage, appropriateness, manageable complexity, testability, and observability. Implementation results showed an increase in school literacy scores to 88.9% (good category) and the birth of a tangible product in the form of a student short story anthology book with QR CBN. These findings confirm that the integration of digital technology-based reading and writing literacy is effective in building a productive and sustainable literacy culture in secondary schools.